Dakwah Bi Al-Hikmah Sebagai Pola Pengembangan Sosial Keagamaan Masyarakat - Bastomi, Hasan (Jurnal Ilmu Dakwah, 2016)
Islam is da’wa religious, its mean obey muslim to preach Islam to other people everytime, everywhere. Dawah can efective if use good method. Dawah method is ways that did by dai (communicator) to mad’u for purpose based hikmah and love. Base on developing religious civil sociaty, implementation of da’wa need significant motivation, methodology and institution. One of them is dawah have to implement with semiotic skill and imagology, with organize sign elements so its interesting and can be mobile everyone to receive Islam and implemen mision of dawah, its remain to do al-khair, ma’ruf and reject al munkar in every dimention. Da’wa like this, summary in word hikmah. Al-hikmah is skill of dai to choose and do technique of  dakwah acording to objective  condition of mad’u and explaine Islamic doctrine and reality in logic argumentation and comunictaive language. Al-Hikmah as a system that unity theoritic and practice skill in da’wa.